KERANGKA STRATEGIS ADOPSI E-GOVERNMENT DALAM MENINGKATKAN EFISIENSI SEKTOR PERTAHANAN - Aris Sarjito (Program Studi Administrasi Negara, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Warmadewa, 2024)
The defense sector, vital for national security, often faces inefficiencies due to outdated processes and limited transparency. This research investigates how E-Government, leveraging digital technologies, can enhance operational efficiency in defense operations. The aim is to develop a strategic framework for E-Government adoption in the defense sector. Employing qualitative research methods using secondary data, the study analyzes existing literature, policy documents, and case studies to evaluate the current state of E-Government implementation. Findings reveal that while some defense organizations have successfully integrated E-Government solutions, challenges persist, including cybersecurity issues and resistance to change. Key factors influencing successful adoption include technological readiness, organizational culture, and policy support. The research identifies that developing a strategic framework involves formulating best practices, guidelines, and actionable recommendations to address these challenges. The proposed framework aims to enhance efficiency by incorporating insights from successful implementations and overcoming identified obstacles. The study concludes that a well-structured strategic framework is essential for effective E-Government adoption, offering a comprehensive approach to improving defense sector operations.